A METHOD OF APPLICATION CASE METHOD AND TEAM BASED PROJECT IN IMPROVING THE QUALITY OF RESEARCH COURSE LEARNING LANGUAGE AND LITERATURE PROGRAM IN EDUCATION STUDIES INDONESIAN LANGUAGE AND LITERATURE - Harisah, Sitti (Tadulako Social Science and Humaniora Journal, 2023)
This research was carried out at the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education Tadulako University, odd semester 2021/2022. The purpose of this study was (1) to determine the application of the Case Method and Team Based Project (CM-TBPj) methods in learning Indonesian Language and Literature Research courses for Indonesian Language and Literature Education Study Program students. (2) to determine the quality of learning outcomes of Indonesian Language and Literature Research courses for Indonesian Language and Literature Education Study Program students through the application of Case Method and Team Based Project (CM-TBPj). This type of research is classroom action research. The flow of this research activity consists of two lines, the first is a case method and a team based project, which is preceded by developing a case framework that will be used in the study of Language and Literature Research courses, then followed by collecting an evaluation test of the quality of learning after the case scenario has been carried out. Data was collected using test and non-test techniques. The research data is in the form of the CM-TBPj learning planning design and its implementation is observed and assessed by peers using the CM-TBPj learning planning and implementation instrument in Indonesian Language and Literature Research learning. The results showed that the planning of CM-TBPj was very well designed with a score of 3.5 and the implementation of CM-TBPj in Indonesian Language and Literature Research learning was carried out very well with a score of 4.0. The results also show that CM-TBPj-based Indonesian Language and Literature Research Learning activities can create an authentic, collaborative, and participatory learning atmosphere in solving real problems/cases in Indonesian Language and Literature Research to achieve course learning objectives (CPMK) with a value of the average student learning outcomes Study Group 1 = 85 (A), Study Group 2 = 88 (A), Study Group 3 = 87 (A), Study Group 4 = 88 (A), and Study Group V = 90 (A ).